Internalisasi Budaya Siri’ Na Pacce dalam Membangun Karakter Mahasiswa di Perguruan Tinggi - Syamsunardi Syamsunardi (UNIVERSITAS NEGERI MAKASSAR, 2022)
Local culture is a source of the richness and diversity of Indonesian culture. Internalization of local culture in formal education is needed to build student character. The aims of this study were: 1) to find out the meaning of the siri' na pacce culture of the Makassarese tribe, 2) to internalize the siri' na pacce culture to students. This study uses an ethnographic approach. The results of this study: 1) siri' is defined as shame, the word na as a connecting word is interpreted as